The Interrelation of an Individual’s Thoughts Features and Behavior in a Conflict Situation - Tevosyan, Maria (Bulletin of Yerevan University E: Philosophy, Psychology, 2013)
The interrelation issue of different thoughts features and behavioral strategies from the viewpoint of conflict situation resolution is discussed in the article by highlighting the importance of the study of that issue in effective conflict resolution and individual’s development processes. Various approaches in a conflict resolution on an individual’s behavior strategies are analyzed by pointing out the most effective ways from the viewpoint of conflict resolution, the study results of the issue mentioned above and their psychological analysis are presented as well.